Effects of plant regulators on the physicochemical characteristics of watermelon fruits, in the São Francisco (Research, Society and Development, 2020)
The objective of this work was to evaluate the effects of four plant regulators-2,4-D; NAA; GA3 and STIMULATE- on the physicochemical characteristics of the watermelon cultivars, Crimson Sweet and Charleston Gray. The experiment was carried out in the field of DTCS-UNEB, Juazeiro-Bahia, between January and April 2011. Polypropylene trays with Vivatto substrate were used to prepare the seedlings. The experimental design was in randomized blocks, with nine treatments and three replications; thus, three plants were placed in each plot, in soil of the type Neossolo Flúvico, totaling eighty-one plants useful for each area, which were irrigated by drip and fertilized by fertigation. The spacing was 3.00 m between lines and 0.80 m between plants. From the flowering of the plants, treatments were carried out with two concentrations for each plant regulator. For physical and chemical analysis the fruits were harvested from the 72nd day after flowering. The results were subjected to analysis of variance and the means compared by the Duncan test at 5% probability. It was found that treatments with 2,4-D caused weakness in the plants, leading some of them to death, which suggests a possible phytotoxic effect of this regulator in the concentrations used. Regarding NAA and the biostimulant, it was found that NAA promoted the inhibition of fruiting and the biostimulant did not promote the development of plants and fruits in relation to the control. GA3 increased soluble solids with a consequent increase in the “ratio”, contributing to the improvement in the taste of watermelon fruits.